2007
DOI: 10.1007/s00035-007-0743-9
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of montane fen meadows by mowing remains possible after 4–35 years of abandonment

Abstract: Billeter R., Peintinger M. and Diemer M. 2007. Restoration of montane fen meadows by mowing remains possible after 4-35 years of abandonment. Bot. Helv. 117: 1 -13.The abandonment of management in Swiss fen meadows has reduced their plant species diversity and the fitness of some typical fen species. We examined whether the resumption of mowing can reverse these effects, and if so, which mechanisms are responsible for community change; we also tested whether restoration success depends on the duration since ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
33
1
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 37 publications
7
33
1
1
Order By: Relevance
“…Our results showed that yearly mowing supports the overall species richness of forbs and target forbs in both meadow types which is in line with other studies (Billeter et al, 2007;Mašková et al, 2009). More forb species proved to be significant character species for mown stands than for abandoned ones in both meadow types.…”
Section: Specific Responses To Mowingsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results showed that yearly mowing supports the overall species richness of forbs and target forbs in both meadow types which is in line with other studies (Billeter et al, 2007;Mašková et al, 2009). More forb species proved to be significant character species for mown stands than for abandoned ones in both meadow types.…”
Section: Specific Responses To Mowingsupporting
confidence: 93%
“…It is also stressed that responses of plants to mowing can be highly specific. Some of the studies indicated that some target species were suppressed by regular mowing, which is generally underrated in light of the increase of species richness (Billeter et al, 2007;Diemer et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While frequent burning promoted cryptogam richness, cover and abundance, mowing with retained slash led to levels similar to those in less-frequently disturbed plots. By contrast, studies elsewhere have found that mowing promoted bryophyte biomass and cover (Huhta et al 2001;Peintinger and Bergamini 2006;Billeter et al 2007). Similarly, a number of grazing-exclusion studies have demonstrated substantial declines in the cover and diversity of soil bryophytes and lichens following increases in vascular plant cover (Brodo 1961;Looman 1964).…”
Section: Mowing Versus Burningmentioning
confidence: 77%
“…Bakker 1989); here we focus only on those studies in which some practical aspects for post-restoration are discussed. The most important effect of grazing and mowing is the reduction of aboveground biomass (Diemer et al 2001;Bonanomi et al 2006;Billeter et al 2007). A common phenomenon in grassland restorations is that an accumulation of plant biomass and litter of sown grasses can be observed from the first year onwards.…”
Section: Grazing and Mowingmentioning
confidence: 99%